Neoadjuvant and adjuvant end-points in health technology assessment in oncology - Harbeck, Nadia; Schneeweiss, Andreas; Thuss-Patience, Peter; Miller, Kurt; Garbe, Claus; Griesinger, Frank; Eberhardt, Wilfried E. E.; Klussmann, Jens P.; Wollenberg, Barbara; Grimm, Marc-Oliver; Zander, Thomas; Lüftner, Diana (European journal of cancer, 2021)
Health technology assessment (HTA) of clinical and economic value of a new intervention is an integral step in providing the access of patients to innovative cancer care and treatment. Overall survival (OS) is the preferred criterion for demonstrating the therapeutic efficacy in HTA given its direct clinical and patient relevance. However, with often long life expectancy of patients with early cancer, analysis of OS becomes less practical. Partially due to this reason, pathological complete response (pCR) and time-to-event end-points like disease-free survival are frequently incorporated into the pivotal clinical trials in the neoadjuvant and adjuvant settings. However, there exists a discrepancy between different national HTA bodies regarding the acknowledgement of patient relevance of these end-points. In this article, we analysed the perspectives of patients on different aspects of end-points used in clinical trials in early cancer. Gathered evidence strongly suggests that complete tumour eradication and reduced risk of recurrence provide important psychological benefits thus signifying that pCR and time-to-event end-points are directly relevant to patients. Additionally, we reviewed opinions on patient relevance of neoadjuvant and adjuvant therapy end-points adopted by HTA bodies during the recent evaluations. We found that improvements in end-points used in the adjuvant setting were commonly considered as valuable to patients. In contrast, opinions on patient relevance of neoadjuvant therapy end-points varied between the national HTA bodies. Universal acknowledgement of patient relevance of therapeutic end-points for early cancer by HTA bodies is necessary to balance the inequality in uptake of innovative therapies into national healthcare systems.
Gesehen am 11.05.2021